Physical quality of soil under secondary forest, leguminous trees, and degraded pasture - Faustino, Lucas Luís; Marciano, Claúdio Roberto; Andrade, Gabriel Ramatis Pugliese (Pesquisa Agropecuaria Brasileira, 2021)
The objective of this work was to assess the efficiency of revegetation with forest leguminous species, for the recovery of the physical quality of a Typic Hapludult under degraded pasture, located in a steep-slope tropical landscape in Southeastern Brazil. Soil samples were collected at the 0–0.10 m and 0.10–0.20 m depths, in areas under Acacia auriculiformis (northern black wattle), Mimosa caesalpiniifolia (“sabiá”), Inga edulis (“ingá”), secondary forest (“capoeira”), and degraded pasture. Tensile strength (TS) was evaluated in soil aggregates of the size classes 8.0–12.5 mm and 12.5–19.0 mm, for the variables TS 8 and TS 12.5, respectively. The lowest mean values of both variables always occurred under the pasture cover (TS 8 of 37.1 kPa and TS 12.5 of 22.7 kPa, for the 0–0.10 m soil layer; and TS 8 of 39.2 kPa and TS 12.5 of 22.8 kPa, for the 0.10–0.20 m soil layer). The highest TS mean values were obtained under the “capoeira” cover (TS 8 of 62.2 kPa, for the 0–0.10 m soil layer) and “sabiá” cover (TS 12.5 of 46.0 kPa, for the 0–0.10 m soil layer; and TS 8 of 53.0 kPa and TS 12.5 of 51.4 kPa, for the 0.10–0.20 m soil layer). Land revegetation with leguminous trees recovers the soil physical quality, since the TS values under the evaluated covers are predominantly closer to those of the secondary forest than to those of the degraded pasture.